Inhibitor of Striatal-Enriched Protein Tyrosine Phosphatase, 8-(Trifluoromethyl)-1, 2, 3, 4, 5-Benzopentathiepin-6-Amine hydrochloride (TC-2153), Produces Antidepressant-Like Effect and Decreases Functional Activity and Protein Level of 5-HT2A Receptor in the Brain. (1st December 2018) - Kulikova, E.A.; Khotskin, N.V.; Illarionova, N.B.; Sorokin, I.E.; Bazhenova, E.Y.; Kondaurova, E.M.; Volcho, K.P.; Khomenko, T.M.; Salakhutdinov, N.F.; Ponimaskin, E.; Naumenko, V.S.; Kulikov, A.V.
Highlights: TC-2153 administration attenuates 5-HT2A receptor functional activity in the brain. Chronic TC-2153 administration produces antidepressant-like effect. TC-2153 decreases the DOI-induced c-Fos expression in the primary neuron cultures. Abstract: The serotoninergic 5-HT2A receptor is involved in the mechanism of depression and antidepressant drugs action. Earlier we showed that striatal-enriched protein tyrosine phosphatase (STEP) inhibitor – 8-(trifluoromethyl)-1, 2, 3, 4, 5-benzopentathiepin-6-amine hydrochloride (TC-2153) affects both the brain serotoninergic system and the brain-derived neurotropic factor that are known to be involved in the psychopathology of depression. In the present study we investigated the effects of chronic TC-2153 administration on behavior in the standard battery of tests as well as the effects of acute and chronic TC-2153 treatment on the brain 5-HT2A receptors in mice. We obtained a prominent antidepressant-like effect of chronic TC-2153 treatment in the forced swim test without any adverse side effects on locomotor activity, anxiety, exploration, motor skill and obsessive–compulsive-like behavior. Moreover, both acute and chronic TC-2153 administration inhibited the functional activity of 5-HT2A receptors estimated by the number of 2, 5-dimethoxy-4-iodoamphetamine (DOI, agonist of 5-HT2A receptors)-induced head-twitches. TC-2153 treatment also attenuated the DOI-induced c-fos expression in cortical and hippocampal neurons and reduced the 5-HT2A receptor protein level in the hippocampus and frontal cortex, but not in the striatum. Taken together, our combined data demonstrate that the antidepressant effect of STEP inhibitor TC-2153 could be mediated by its inhibitory properties towards the 5-HT2A receptor-mediated signaling.